Genetic Variation at Chromosome 2q13 and Its Potential Influence on Endometriosis Susceptibility Through Effects on the IL-1 Family. (September 2018) - Gajbhiye, Rahul; McKinnon, Brett; Mortlock, Sally; Mueller, Michael; Montgomery, Grant
Endometriosis is characterized by the growth of epithelial and stromal cells outside the uterine cavity. It has a complex etiology and affects ∼10% of reproductive age women. It is accompanied by a chronic inflammatory response with substantial evidence to indicate genetic susceptibility. The causal genes and their pathways leading to endometriosis, however, are still unknown. Recently, genomewide association studies on endometriosis identified 14 genomic risk loci in women of European and Japanese ancestry. It is becoming increasingly clear that these risk regions are intergenic and thus contribute to disease susceptibility through regulatory mechanisms, most likely mediated through regulation of genes within a restricted distance from the risk variants. One endometriosis risk locus has been detected at chromosome 2q13 within an inflammatory-rich region of gene transcripts and thus may play a role in the inflammation component of the disease. We carried out detailed analysis of the genomic region 250 kb on either side of sentinel SNP rs10167914 and identified 21 transcripts which contained 6 interleukin (IL)-1 family genes, 3 previously reported coding genes that have a relationship to inflammation, 4 novel coding, or pseudogenes, and 8 noncoding RNA transcripts. Through an extensive literature search, we examined the roles these genes and their resultant proteins play in endometriosis pathogenesis. The results suggest alteration in the expression the IL-1 family transcripts either alone or as a complex milieu could have a significant influence on endometriosis and should be prioritized for future study on the implications of inflammation on endometriotic lesions.